Research trends in sports sciences in Indonesia: A bibliometric analysis - Jumareng, Hasanuddin; Setiawan, Edi; Supriyadi, Edi; Sugiarni, Rani; Abdullah, Khairul Hafezad; Gazali, Novri; Ridwan, Mochamad; Demir, Gí¶ní¼l TekkurÅŸun; Hofmeister, Martin (Universitas Negeri Yogyakarta, 2024)
This study presents a comprehensive bibliometric analysis of research trends in the field of sport science in Indonesia. Using a bibliometric approach, 128 relevant articles were collected, consisting of articles published in journals, written in English, and originating from Indonesia. This research focuses on analysing publication patterns and trends, with particular emphasis on publication year, affiliated institutions, and leading authors in the field of sport science. The analysis showed that 2020 was the year with the highest number of publications, indicating an increased interest and dedication to sport science research in Indonesia during that period. Among the various educational institutions contributing to this field, Universitas Negeri Yogyakarta emerged as the leading campus with the highest number of publications, demonstrating its important role in advancing sport-related studies. Additionally, the study identified